Methods of Narrating Hadith - Wafik Azizah; Yossi Kurnia Yudatama (al-Afkar, Journal For Islamic Studies, 2024)
The existence of  Hadits is one of the source of law in Islam, where Hadits is the second source after the al-Qur’an. Efforts to transmit the Prophet’s Hadits also go through a process that starts from the generation of friends to the tabi’in generation and then to the tabi’in generation. In terms of narration, the narrator contributes fully to learning whether a hadist is good or not. There are two elements that must be know in the narration of hadist, namely Tahammul al-Hadist wa al-Ada’. From this, the author will discuss the methods must be used. In Tahammul al-Hadist wa al-Ada’ these methods are divided into eight methods, including: 1). Al-Sima’ min Lafzh al-syaykh, 2). Al-Qira’ah ‘ala al-syaykh, 3). Al-Ijazah, 4). Al-Munawalah, 5). Al-Mukatabah, 6). Al-I’lam, 7). Al-Washiyyah,  dan yang terakhir 8). Al-Wijadah.